Quantitative paradigm in researchs: whether the «crisis of the number?» is overcome - G. V. Varganova (Библиосфера, 2014)
The author considers the problems, connected with researches within the framework of the quantitative para- digm. The main methods of the quantitative studies are defined, their advantages and disadvantages when ap- plied to the subject of the study are emphasized. The questions of research training of specialist with higher education are underlined.